GENERAL CONCEPTS OF PLANT EVOLUTION AND THEIR STRUCTURE DAUGHTER - Ismailova Saida Ulug‘bek qizi (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
If I give a general understanding of the evolution of plants and their structure, since the 50s of the last century, a number of scientists have been working on the evolution of plants, and by introducing their concepts into science, they have made the evolutionary system of plants much clearer. enriched with limes.